Recent advances in protein and amino acid nutritional dynamics in relation to performance, health, welfare, and cost of production - Roshan Adhikari; Sam J. Rochell; Ruben Kriseldi; Marcelo Silva; Laura Greiner; Chance Williams; Bart Matton; Annalise Anderson; Gisela F. Erf; Eunyoung Park; Keith Haydon; Jason Lee (Poultry Science)
Amino acids are the foundation of numerous metabolic and physiological pathways for skeletal muscle accretion, internal organ development, skeletal development, and immune function. One widely studied subject in monogastric nutrition is dietary crude protein. However, birds do not have a crude protein requirement but have a clear requirement for essential amino acids. As individual amino acid requirements of swine and poultry are investigated and modern feed formulation tools and feed-grade amino acids are available cost-effectively, the dynamics of how we look at crude protein in the feed have evolved. With the modern tools available, nutritionists are able to formulate the feed to meet the amino acids required for optimal performance of animals. This approach reduces the excess nitrogen in the feed, making the diets friendlier for the gut, reducing substrates for harmful proliferating bacteria, reducing nitrogen excretion in manure, and improving the ecology and sustainability. Apart from growth, amino acids have a functional role in the metabolic and physiological pathways. Amino acids like threonine and arginine have additional functional roles in intestinal turnover, immune function, wound healing, vasodilation and oxidative, and heat stress alleviation. Such specific amino acids can be increased in the diet to support the physiological needs during the growth of animals without increasing the unwanted dietary nitrogen content. As the industry moves toward reducing crude protein while meeting the essential amino acid needs, more research is needed to understand the requirement of specific lower limiting and non-limiting amino acids as well as the dynamics of those amino acids in health, welfare, cost of production and ecological impact in poultry and swine production.